GRAVITY, PROBABILITY AND CONSCIOUSNESS - Prashant (International Journal of Research -GRANTHAALAYAH, 2018)
The theory of special connectivity [1] has been mathematically verified with the help of probability. With an example of tossing a coin, how consciousness manipulates probability has been discussed. Paper is based on a fact that the observer influences the observed. .